LINGUAL-CULTURAL ASPECT OF THE LANGUAGE OF MEDICAL SPHERE (The New Uzbekistan Journal of Medicine, 2025)
This article is devoted to the study of physician’s communication manner, medical deontology, doctor-patient relationship, the relationship of doctor with the relatives of patient, medical ethics, the role of psychotherapy in physician’s work, linguacultural aspect of medical language, the linguacultural speech result of euphemism.